anonymous
  • anonymous
If f(x) = x − 4 and g(x) = 1 over 2x − 2, find f[g(−6)].
Mathematics
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this
and thousands of other questions.

anonymous
  • anonymous
If f(x) = x − 4 and g(x) = 1 over 2x − 2, find f[g(−6)].
Mathematics
schrodinger
  • schrodinger
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this
and thousands of other questions

bahrom7893
  • bahrom7893
g(-6) = 1/(2*(-6)-2) = 1/(-12-2) = -1/14
bahrom7893
  • bahrom7893
f [g(-6)] = f [ -1/14] = (-1/14) - 4
anonymous
  • anonymous
-4 isnt an option.

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
9 3 −9 −3
bahrom7893
  • bahrom7893
Well did I say 4 is the answer? whatever -1/14 - 4 is.. wait
bahrom7893
  • bahrom7893
By the way is it: |dw:1352646754665:dw|
anonymous
  • anonymous
first one
bahrom7893
  • bahrom7893
oh, then scratch what i did before, and use parenthesis when you post the question
bahrom7893
  • bahrom7893
f(g(-6)) = 1/[2*(-6)] - 2 = (-1/12) - 2 = (-1/12) + (-24/12) = -25/12
bahrom7893
  • bahrom7893
wait that's just g(-6)
bahrom7893
  • bahrom7893
now: f(g(-6)) = f(-25/12) = -25/12 - 4 = (-25 - 48)/12 = -73/12... i don't see where i'm going wrong.
bahrom7893
  • bahrom7893
@UnkleRhaukus can u go over this real quick?
UnkleRhaukus
  • UnkleRhaukus
all of it?
bahrom7893
  • bahrom7893
lol i guess u can just solve the question, i don't see what i did wrong, because i am not getting any of his options
anonymous
  • anonymous
i sent them to you
anonymous
  • anonymous
9 3 −9 −3
bahrom7893
  • bahrom7893
like i said, im not getting any of the options......
UnkleRhaukus
  • UnkleRhaukus
\[g(x)=\frac1{2x}−2\] \[g(−6)=\frac1{2(-6)}−2=-\frac{1}{12}-2=\frac{-36}{12}=\color\gray{-3}\]
bahrom7893
  • bahrom7893
unkle.... are you sure you added those right?
UnkleRhaukus
  • UnkleRhaukus
hmm, no
UnkleRhaukus
  • UnkleRhaukus
\[g(−6)=\frac1{2(-6)}−2=-\frac{1}{12}-\frac{24}{12}=\frac{-25}{12}\]
UnkleRhaukus
  • UnkleRhaukus
\[f(-25/12)=-\frac{25}{12}-4=-\frac{25}{12}-\frac{48}{12}=-\frac{25+48}{12}\color\grey=\color{white}{\frac{-73}{12}}\]
UnkleRhaukus
  • UnkleRhaukus
im getting what you are getting now bahrom
anonymous
  • anonymous
how about this one If f(x) = −2x − 4 and g(x) = x + 4, find (f over g)(−8).
anonymous
  • anonymous
options are −3 3 −1 1
UnkleRhaukus
  • UnkleRhaukus
what do you mean by 'over'
UnkleRhaukus
  • UnkleRhaukus
do you mean \(f\circ g\)
anonymous
  • anonymous
f/g
UnkleRhaukus
  • UnkleRhaukus
f(x) = −2x − 4 g(x) = x + 4 (f / g)(x) = ( −2x − 4 ) / ( x + 4) (f / g)(−8) = ( −2(-8) − 4 ) / ( (-8) + 4)
anonymous
  • anonymous
wats the answer
anonymous
  • anonymous
??
UnkleRhaukus
  • UnkleRhaukus
( −2(-8) − 4 ) / ( (-8) + 4) =( 16 − 4 ) / ( -4) =

Looking for something else?

Not the answer you are looking for? Search for more explanations.